The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1089/vim.2006.0078
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses to Replication of Porcine Reproductive And Respiratory Syndrome Virus in Isolated Swine Alveolar Macrophages

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is an infectious disease caused by a positive RNA strand arterivirus. PRRS virus (PRRSV) interacts primarily with lung macrophages. Identifying the genetic components involved in host resistance/susceptibility would represent an important step forward in the design of disease control programs. In this study, alveolar macrophages derived from five commercial pig lines were used to study the innate immune response to PRRSV infection in vitro. Analysis by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 62 publications
3
61
0
1
Order By: Relevance
“…PRRSV replicates in porcine macrophages and induces several cytokines including IL-6, IL-8, IL-10, and TNF-a involving pulmonary inflammation response [16,17]. NF-jB is a critical transcription factor regulating the transcription of many proinflammatory molecules that are thought to be important in the generation of inflammation, including certain adhesion molecules (ICAM-1), most cytokines (TNF-a, IL-6), and chemokines (IL-8) [18].…”
Section: Discussionmentioning
confidence: 99%
“…PRRSV replicates in porcine macrophages and induces several cytokines including IL-6, IL-8, IL-10, and TNF-a involving pulmonary inflammation response [16,17]. NF-jB is a critical transcription factor regulating the transcription of many proinflammatory molecules that are thought to be important in the generation of inflammation, including certain adhesion molecules (ICAM-1), most cytokines (TNF-a, IL-6), and chemokines (IL-8) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that there is significant interbreed variation in monocyte function in pigs that could be important in innate immunity (22). Accordingly, we sampled PBMCs from at least two individual animals from six different breeds.…”
Section: Identification Of Monocyte Subpopulations In the Pigmentioning
confidence: 99%
“…Methods and models for this analysis are described by Detilleux (2011). Studies by Doeschl-Wilson et al (2009), Ait-Ali et al (2007, Vincent et al (2006), Opriessnig et al (2006) and Halbur et al (1998) suggest differences in host genetic response with respect to porcine reproductive and respiratory syndrome and postweaning multisystemic wasting syndrome in view of breeding for improved resistance.…”
Section: New Phenotypesmentioning
confidence: 99%